Genomic Regions Influencing Seminal Root Traits in Barley. Issue 1 (1st March 2016) - Robinson, Hannah; Hickey, Lee; Richard, Cecile; Mace, Emma; Kelly, Alison; Borrell, Andrew; Franckowiak, Jerome; Fox, Glen
Abstract : Water availability is a major limiting factor for crop production, making drought adaptation and its many component traits a desirable attribute of plant cultivars. Previous studies in cereal crops indicate that root traits expressed at early plant developmental stages, such as seminal root angle and root number, are associated with water extraction at different depths. Here, we conducted the first study to map seminal root traits in barley ( Hordeum vulgare L.). Using a recently developed high‐throughput phenotyping method, a panel of 30 barley genotypes and a doubled‐haploid (DH) population (ND24260 × 'Flagship') comprising 330 lines genotyped with diversity array technology (DArT) markers were evaluated for seminal root angle (deviation from vertical) and root number under controlled environmental conditions. A high degree of phenotypic variation was observed in the panel of 30 genotypes: 13.5 to 82.2 and 3.6 to 6.9° for root angle and root number, respectively. A similar range was observed in the DH population: 16.4 to 70.5 and 3.6 to 6.5° for root angle and number, respectively. Seven quantitative trait loci (QTL) for seminal root traits (root angle, two QTL; root number, five QTL) were detected in the DH population. A major QTL influencing both root angle and root number ( RAQ2 / RNQ4 ) was positioned on chromosome 5HL. Across‐species analysis identified 10 common genes underlying root trait QTL in barley, wheat ( Triticum aestivum L.), and sorghum [ Sorghum bicolor (L.) Moench]. Here, we provide insight into seminal root phenotypes and provide a first look at the genetics controlling these traits in barley.